2018
DOI: 10.1017/s0272263118000116
|View full text |Cite
|
Sign up to set email alerts
|

L2 Development of Perceptual Categorization of Dialectal Sounds

Abstract: The present study examined second language (L2) development in the perceptual identification of a dialectal sound of the target language, through an investigation of the role of individual learner experiences in L2 phonological development. A total of 213 English-speaking learners of Spanish across five levels of study and with varying dialect contact experiences completed an identification task, which tested perceptual categorization of Spanish dialectal aspirated-s (e.g., siesta [ˈsi̯eh-ta]). In accordance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 33 publications
4
17
0
Order By: Relevance
“…Additionally, L2 processing and interpretation patterns are often different from those of NSs (e.g., Clahsen & Felser, 2006; Grüter, Lew-Williams, & Fernald, 2012). As would be expected, given what is known about variable structures in L2s, interpretation may further be affected by implicit language attitudes, by individual identities, and by experiences and contact with particular speech communities (Schmidt, 2018; Schoonmaker-Gates, 2017). It is important to note that the term interpretation may be used to refer to online processing as well as more deliberate interpretation of meaning (or implied meaning), both linguistic and social, and this range of constructs further contributes to the variety of studies included under the umbrella term.…”
Section: Research On Interpretationmentioning
confidence: 93%
“…Additionally, L2 processing and interpretation patterns are often different from those of NSs (e.g., Clahsen & Felser, 2006; Grüter, Lew-Williams, & Fernald, 2012). As would be expected, given what is known about variable structures in L2s, interpretation may further be affected by implicit language attitudes, by individual identities, and by experiences and contact with particular speech communities (Schmidt, 2018; Schoonmaker-Gates, 2017). It is important to note that the term interpretation may be used to refer to online processing as well as more deliberate interpretation of meaning (or implied meaning), both linguistic and social, and this range of constructs further contributes to the variety of studies included under the umbrella term.…”
Section: Research On Interpretationmentioning
confidence: 93%
“…Schmidt (2018) found in a crosssectional L2 perception study of aspirated-/s/ that the American English learners of Spanish did not acquire the perceptual mapping or association of syllable-final aspirated [h] forms to Spanish /s/ until late levels of proficiency (third-year university Spanish courses or above), if at all-and frequently "ignored" syllable-final [h] or perceived it as Spanish "f." Indeed, though all students in the current study reported awareness of the local dialectal pronunciation of "y" and "ll," only one-third reported awareness of the local pronunciation of syllable-final "s." It is argued, thus, that a major contributor to why the learners in the current study did not produce the local /s/-lenited variants [h ϕ] by the end of the shortterm study abroad period-and why Geeslin and Gudmestad (2011) also found low levels of use-is the low phonetic saliency, or acoustic prominence, of these phones for English speakers (due potentially to the position of the aspirated cue at the end of a syllable or a word, a less salient position (Cutler, 1982), and to its likely association with the previous vowel for English speakers and is as such "ignored" as a consonant segment (see L. B. Schmidt, 2018)). Thus, this low phonetic saliency results in a lack of noticing or awareness of the lenited-/s/ forms by the L2 learners-which, of course, is argued to be a critical condition for learning to occur (see the Noticing Hypothesis; R. Schmidt, 1990).…”
Section: Adoption Of Regional Variants Of Buenos Aires Spanishmentioning
confidence: 99%
“…One possible limitation was the two-forced choice alternatives offered as possible answers. Schmidt (2018), other than a lexical identification task, employed a categorization task with nonsense words in her study, in which she provided further response alternatives to [s] and [V]. Even when she used citation-form words, the fact that she included [f] as a possible answer enabled her to see that aspiration was noticed, although not associated to /s/.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from this study, research on the perception of L2 Spanish aspiration has been dedicated to other Spanish varieties. Schmidt (2018) studied the aspiration of coda /s/ in citation-form words of Argentinian and Venezuelan Spanish by speakers of GAE, in relation to their level of proficiency (levels 1–5). Results indicate that not until level 3 do listeners start to identify this dialectal feature and not until level 5 do listeners perform similarly to native speakers of the dialect.…”
Section: Sociophonetic Variation In Speech Perceptionmentioning
confidence: 99%